Treatment Of Cekehan (Cough) Based On The Local Activity Of Bali In Usada Tenung Tanyalara - I Made Slamet Putra Prasetya (Universitas Islam Jember, 2021)
Usada Tenung Tanyalara is a form of Balinese local wisdom which contains traditional Balinese medicine. Usada Tenung Tanyalara is still limited to the name of the disease, the ingredients used to treat disease processing methods, as well as empirically proven uses. It is important to carry out further studies related to the existing treatment at Usada Tenung Tanyalara. Cough or in Balinese called Cekehan is a reflex response of the body's defense to remove foreign objects from the respiratory tract that protects the lungs from foreign objects from the gastrointestinal tract and upper respiratory tract. Coughing can be caused by infection and not infection. Cough treatment in Usada Tenung Tanyalara is with raw chicken egg whites, green skin coconut milk and temu tin (temu putih) rhizome. The albumin content in chicken egg whites can reduce cough complaints and increase the immune system through the mechanism of increasing the circulatory system to help metabolize nutrients, and accelerate tissue recovery. The rhizome of temu putih (temu tin) has anti-inflammatory activity, thereby reducing cough symptoms accompanied by mucosal secretions. Coconut milk has antibacterial properties so it can suppress the pathogenic bacteria that cause coughs. Based on the properties of cough medicine ingredients in Balinese local wisdom, namely Usada Tenung Tanyalara, it is proven to have a pharmacological effect to cure coughs. Keywords: Coughs, Usada Bali, Usada Tenung Tanyalara, Traditional medecine